2012
DOI: 10.1128/iai.00231-12
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Actin-Plasma Membrane Association in Pseudomonas aeruginosa Infection and Type III Secretion Translocation in Migratory T24 Epithelial Cells

Abstract: ABSTRACTThe opportunistic pathogenPseudomonas aeruginosatargets wounded epithelial barriers, but the cellular alteration that increases susceptibility toP. aeruginosainfection remains unclear. This study examined how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…RalA can be ADP-ribosylated by Pa ExoS-WT at two to three sites, with Arg52 functioning as a preferred site of ExoS ADP-ribosylation, and Arg135 and Arg161 functioning as secondary sites of ADP-ribosylation (Fraylick et al, 2002a). ADP-ribosylation by ExoS causes RalA to shift in mobility in a manner dependent on the number of sites of ADP-ribosylation (Bridge et al, 2012; Fraylick et al, 2002a), and the different shift in RalA mobility detected between MTC and MTLn3 cells (Fig. 1B, noted by asterisks) can be explained by RalA being ADP-ribosylated at more sites in MTC cells.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…RalA can be ADP-ribosylated by Pa ExoS-WT at two to three sites, with Arg52 functioning as a preferred site of ExoS ADP-ribosylation, and Arg135 and Arg161 functioning as secondary sites of ADP-ribosylation (Fraylick et al, 2002a). ADP-ribosylation by ExoS causes RalA to shift in mobility in a manner dependent on the number of sites of ADP-ribosylation (Bridge et al, 2012; Fraylick et al, 2002a), and the different shift in RalA mobility detected between MTC and MTLn3 cells (Fig. 1B, noted by asterisks) can be explained by RalA being ADP-ribosylated at more sites in MTC cells.…”
Section: Resultsmentioning
confidence: 96%
“…Detection of Pa -T3S translocation into eukaryotic cells requires a 1.5 to 3.5 hr co-culture period, depending on the cell line and the method of analysis (Bridge et al, 2012; Bridge et al, 2010). To adapt Pa co-culture conditions to studies of MTC and MTLn3 cells, indicated infections were performed in medium containing 5% FBS (steady state conditions) to allow cells to move randomly during the co-culture period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the ADPRT activity of ExoS disrupts the epithelial cell barrier [35]. The authors suggest this as the mechanism of PA invasion and dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…RhoGAP activity due to a R146A mutation, or 5) ExoS that lacks catalytic activity (RhoG-/ADPr-) due to E379A/E381A/R146A mutations, were previously described (Bridge, Martin et al 2012). Bacteria were grown at 37°C in Lauria Broth with appropriate antibiotics.…”
Section: Bacteria Strainsmentioning
confidence: 99%